Emergencies in diabetes : diagnosis, management and prevention - Krentz, Andrew J. (J. Wiley, 2004)
"While diabetes can usually be well controlled using modern therapies, metabolic emergencies inevitably occur. This book provides an easy-to-read yet comprehensive account of emergencies in diabetes conveniently collected into one volume. For each topic, a brief review of the pathophysiology is followed by a description of cardinal clinical features, clinical and biochemical assessment and clinical management." "Designed to fit conveniently into the pocket of a white coat, this book should be readily to hand in all hospital medical wards, particularly the emergency department. It will be useful to junior hospital doctors across a wide range of specialties, senior house officers in general medical training, and nurses involved in the care of patients with diabetes."--Jacket